2021
DOI: 10.1016/j.jpedsurg.2021.01.049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intra- and extra-corporeal laparoscopic hernia repair in children: A systematic review and pooled data-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Over the last decades, different methods for laparoscopic IHR have been described, including transperitoneal and extraperitoneal techniques. [1,25,26] In our survey 33% of pediatric surgeons prefer transperitoneal technique using only one trocar for the camera. Four different procedures with 2-3 trocars for intracorporal suturing with or without opening the peritoneum are performed in the study period in Germany.…”
Section: Discussionmentioning
confidence: 87%
“…Over the last decades, different methods for laparoscopic IHR have been described, including transperitoneal and extraperitoneal techniques. [1,25,26] In our survey 33% of pediatric surgeons prefer transperitoneal technique using only one trocar for the camera. Four different procedures with 2-3 trocars for intracorporal suturing with or without opening the peritoneum are performed in the study period in Germany.…”
Section: Discussionmentioning
confidence: 87%
“…[2][3][4]11 Numerous modifications laparoscopic techniques have expanded in the past decade, from multi -port to Single-port, 12,13 with preperitoneal hydrodissection technique, 9,14 into intra-or extra-corporeal closing techniques. 10,15,16 Laparoscopic intra -corporeal suturing technique is the most difficult step in laparoscopic surgery, it needs additional laparoscopic instrument, skilled laparoscopic techniques and long learning curve. 5,10,15 The laparoscopic extra-corporeal closing techniques are easyly operable and yield improvedoutcomes and cosmetic satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a systematic review in 2021 by Maat et al reported a longer duration of surgery in intra-corporeal repair compared with extra-corporeal repair, with the need for intra-corporeal suturing and knotting identi ed as the key time-limiting factor. [24] The intra-corporeal suturing and knotting approach places substantial demands on the requirement of hand-eye coordination, particularly in relation to the posterior and medial hemi-circumference of internal rings; major vessels, such as the iliac and inferior epigastric arteries; and the need to avoid important testicular vasculature-for example, the vas deferens and testicular vessels. With the accumulation of experience and various technical re nements, such as hydro-dissection and the "needle sign," clinical outcomes improve and the operative time of the technique decreases.…”
Section: Discussionmentioning
confidence: 99%